FACING THE HARDEST CHALLENGES IN DIGITAL WORK: CROSS-SECTOR PRACTITIONER-MANAGERS’ INSIGHTS FROM FOCUS GROUP DISCUSSIONS - Sri Yusriani; Hendrian Hendrian; Viktor Peniel Sarimatondang Bancin; Prasetyo Harisandi; Shine Pintor Siolemba Patiro; Lamia Farha (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Digital transformation has fundamentally reshaped work dynamics, yet understanding the toughest challenges managers face in adapting to digital work remains underexplored across sectors. This study investigates the most pressing challenges perceived by practitioner-managers from academia, higher education, international trade, marketing, and technology industries. Using a qualitative approach, we conducted Focus Group Discussions (FGDs) with seven senior managers, all domain experts with substantial leadership experience. Data were thematically analyzed to extract cross-sector insights. Findings reveal that while technological readiness and digital skills gaps are common hurdles, sector-specific issues, such as resistance to change in higher education, cross-border digital compliance in food export businesses, cyber-communication overload in technology management, and balancing data-driven marketing with creativity, compound the challenges. Despite these obstacles, discussions highlight adaptive leadership, collaborative learning, and resilience as pivotal for navigating digital transformation. This research contributes to the understanding of managerial perspectives in digital work transitions and provides practical implications for leadership development and organizational strategy in the digital era.